Enhancing the stability and performance of graphene oxide-poly(amido amine) polysulfone membranes with (3-aminopropyl)triethoxysilane crosslinker - Ahmed T. Yasir (17302753) (2025)
The separation of oil-in-water (O/W) emulsions is a critical focus in industrial water treatment, where ultrafiltration membrane technology is increasingly utilized due to its modularity, cost-effectiveness, and high rejection efficiency. However, balancing membrane permeability, selectivity, and fouling resistance remains a significant challenge, as it directly impacts the membrane's separation performance and longevity. In this study, we present a novel polysulfone-based ultrafiltration membrane incorporating a graphene oxide-poly(amido amine) (GO-PAMAM) nanocomposite, designed to improve water flux and anti-fouling properties. To mitigate concerns of GO-PAMAM leaching, GO was functionalized with (3-aminopropyl) triethoxysilane (APTES), resulting in the generation-zero (Gen 0) GO-APTES-PAMAM nanocomposite. Higher generations (Gen 2, Gen 3, and Gen 4) with increased PAMAM functionalization were synthesized via Michael addition and amidation reactions, as confirmed by X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy. The fabricated membranes were characterized by pore size analysis, water contact angle measurements, scanning electron microscopy (SEM), and atomic force microscopy (AFM). Filtration performance was evaluated using a dead-end filtration setup, revealing that water permeation flux increased with higher PAMAM generations. Notably, the Gen 4 GO-APTES-PAMAM membrane exhibited a 327 % flux enhancement and a 17.3 % improvement in flux recovery rate compared to pristine polysulfone (Psf) membranes along with 97.1 % oil rejection efficiency. Leaching tests demonstrated that APTES functionalization significantly reduced nanocomposite leaching. Fouling analysis using Hermia’s model identified cake formation as the dominant fouling mechanism for all membranes. Surface energy analysis, based on the Owens-Wendt-Kaelble (OWK) model, indicated that the nanocomposite incorporation increased polar surface energy, thereby maintaining high oil rejection even at elevated flux levels. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2025.115989